A Hetero‐Bifunctional Spacer for the Smart Engineering of Carbon‐Based Nanostructures. Issue 4 (4th February 2015) - Tuci, Giulia; Luconi, Lapo; Rossin, Andrea; Baldini, Francesco; Cicchi, Stefano; Tombelli, Sara; Trono, Cosimo; Giannetti, Ambra; Manet, Ilse; Fedeli, Stefano; Brandi, Alberto; Giambastiani, Giuliano
Abstract Invited for this month's cover are collaborators from four different Italian research groups, three at the National Research Council (ICCOM, IFAC, and ISOF) and one at the University of Florence. The cover picture shows a representative cartoon of engineered 1D carbon nanomaterials and their effective surface decoration with (bio)molecules and fluorescent markers. Read the full text of the article at 10.1002/cplu.201402391